2021
DOI: 10.1038/s41586-021-03854-z
|View full text |Cite
|
Sign up to set email alerts
|

Skilful precipitation nowcasting using deep generative models of radar

Abstract: Precipitation nowcasting, the high-resolution forecasting of precipitation up to two hours ahead, supports the real-world socioeconomic needs of many sectors reliant on weather-dependent decision-making1,2. State-of-the-art operational nowcasting methods typically advect precipitation fields with radar-based wind estimates, and struggle to capture important non-linear events such as convective initiations3,4. Recently introduced deep learning methods use radar to directly predict future rain rates, free of phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
393
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(403 citation statements)
references
References 30 publications
8
393
0
2
Order By: Relevance
“…The video GAN model contains sequential components in the generator, while the discriminator uses a dual architecture that distinguishes the real and generated frames to ensure both temporal and spatial consistency. From the case study of connective cells over eastern Scotland, it was observed that using video GAN in the model significantly improved the quality of precipitation forecasts (Ravuri et al, 2021). These studies indicate that the performance of precipitation nowcasting models can be improved by advanced machine learning techniques.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The video GAN model contains sequential components in the generator, while the discriminator uses a dual architecture that distinguishes the real and generated frames to ensure both temporal and spatial consistency. From the case study of connective cells over eastern Scotland, it was observed that using video GAN in the model significantly improved the quality of precipitation forecasts (Ravuri et al, 2021). These studies indicate that the performance of precipitation nowcasting models can be improved by advanced machine learning techniques.…”
Section: Introductionmentioning
confidence: 84%
“…Rüttgers et al (2019) showed that typhoon tracks and cloud patterns over the Korean Peninsula could be successfully predicted using cGAN architecture with satellite cloud images. Ravuri et al (2021) developed a precipitation nowcasting model using a deep generative model inspired by the video GAN model (Clark et al, 2019). The video GAN model contains sequential components in the generator, while the discriminator uses a dual architecture that distinguishes the real and generated frames to ensure both temporal and spatial consistency.…”
Section: Introductionmentioning
confidence: 99%
“…If the time features such as month and hour are also set by the one-hot encoding method, a large feature space will be occupied. Moreover, the temporal continuity such as between December and January will be destroyed if the month feature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) is directly mapped into the interval of 0-1. In this work, clock projection is utilized to extract the temporal features.…”
Section: Additional Spatiotemporal Feathersmentioning
confidence: 99%
“…Weather prediction is of great importance and can affect some aspects of daily life, such as air quality, travel plans, energy supply, and so on [1][2][3][4]. A conventional prediction method is numerical weather prediction (NWP) method, which solves the numerical solutions of atmospheric hydro-thermo dynamic equations to predict meteorological dynamics [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The NNs were shown to be particularly successful in precipitation nowcasting. For example, Ravuri et al [21] used radar data to perform short-range probabilistic predictions of precipitation, while Sønderby et al [22] combined radar data with the satellite data.…”
Section: Introductionmentioning
confidence: 99%